The Role of Race, Ethnicity, and Party on Attitudes Toward Descriptive Representation. (January 2015) - Casellas, Jason P.; Wallace, Sophia J.
Using original survey data from the Cooperative Congressional Election Survey (CCES), we examine variation in racial and ethnic group and partisan attitudes toward legislators and representation. Respondents were asked about their views on descriptive representation, its importance for their own elected official, and whether it was important to have more descriptive representatives in general. Using respondents' personal characteristics such as education, partisanship, race, ethnicity, income, and race and ethnicity of their House of Representatives member, we analyze the impact of these variables on attitudes toward representation. We find that Latino and Black respondents place a high level of importance on having descriptive representatives in their own districts in addition to articulating a high degree of importance to having more representatives from their respective group. However, Latino Republicans place less importance on descriptive representation overall than Latino non-Republican respondents. Non-Latino Republicans also place importance on more legislators of their same race or ethnicity. The findings have implications for democratic governance as the demographics of the United States rapidly changes.